Folic acid supplementation rescues valproic acid‐induced developmental neurotoxicity and behavioral alterations in zebrafish embryos. (16th May 2021) - Muhsen, Maram; Youngs, Jaclyn; Riu, Anne; Gustafsson, Jan‐Åke; Kondamadugu, Vijay Sai; Garyfalidis, Elefterios; Bondesson, Maria
Abstract: Objective: Fetal exposure to the anticonvulsant drug valproic acid (VPA), used to treat certain types of epilepsy, increases the risk for birth defects, including neural tube defects, as well as learning difficulties and behavioral problems. Here, we investigated neurotoxic effects of VPA exposure using zebrafish as a model organism. The capacity of folic acid (FA) supplementation to rescue the VPA‐induced neuronal and behavioral perturbations was also examined. Methods: Zebrafish embryos of different transgenic lines with neuronal green fluorescent protein expression were exposed to increasing concentrations of VPA with or without FA supplementation. Fluorescence microscopy was used to visualize alterations in brain structures and neural progenitor cells, as well as motor neurons and neurite sprouting. A twitching behavioral assay was used to examine the functional consequences of VPA and FA treatment. Results: In zebrafish embryos, VPA exposure caused a decrease in the midbrain size, an increase in the midline gap of the hindbrain, and perturbed neurite sprouting of secondary motor neurons, in a concentration‐dependent manner. VPA exposure also decreased the fluorescence intensity of neuronal progenitor cells in early developmental stages, indicating fewer cells. Furthermore, VPA exposure significantly altered embryonic twitching activity, causing hyperactivity in dark and hypoactivity in light. Supplementation of FA rescued the VPA‐induced smaller midbrain size and hindbrain midline gap defects. FA treatment also increased the number of neuronal progenitor cells in VPA‐treated embryos and salvaged neurite sprouting of the secondary motor neurons. FA rescued the VPA‐induced alterations in twitching activity in light but not in dark. Significance: We conclude that VPA exposure induces specific neurotoxic perturbations in developing zebrafish embryos, and that FA reversed most of the identified defects. The results demonstrate that zebrafish is a promising model to study VPA‐induced teratogenesis and to screen for countermeasures.